25-Hydroxyvitamin D assays: Potential interference from other circulating vitamin D metabolites. Issue 164 (November 2016) - Carter, G.D.; Jones, J.C.; Shannon, J.; Williams, E.L.; Jones, G.; Kaufmann, M.; Sempos, C.
Highlights: Both 3- epi -25-OHD3 and 24, 25-dihydroxyvitamin D (24, 25(OH)2 D) show a strong correlation with 25-OHD3 . 3- epi -25-hydroxyvitamin D(3- epi -25-OHD) does not cross react in immunoassays for 25-hydroxyvitamin D (25-OHD). Some HPLC/UV and LC–MS/MS methods may not resolve 3- epi -25-OHD3 from 25-OHD3 . Cross reaction of 24, 25(OH)2 D in 25-OHD immunoassays may contribute to the positive bias of some assays, particularly at high 25-OHD concentrations. The use of exogenous 24, 25(OH)2 D gives misleading results in recovery experiments. Abstract: The vitamin D External Quality Assessment Scheme (DEQAS) for 25-hydroxyvitamin D (25-OHD) has approximately 1100 participants in 53 countries using 26 different methods or variants of methods (October 2014). In April 2015, the scheme was extended to cover 24, 25-dihydroxyvitamin D (24, 25(OH)2 D). Since 2013, the 25-OHD scheme has been accuracy-based with values assigned by the NIST reference measurement procedure (RMP). DEQAS is uniquely placed to assess the accuracy (bias) and specificity of 25-OHD methods in a routine laboratory setting. Other vitamin D metabolites are known to interfere in 25-OHD assays and DEQAS has distributed samples spiked with 3- epi -25-OHD3 (52.4 nmol/L), 24R, 25(OH)2 D3 (14.4 nmol/L) and 24S, 25(OH)2 D3 (57.9 nmol/L). The 3-epimer showed a cross reactivity of 56% in a competitive protein binding assay but was not detected in any antibody-based methods. Not all HPLC/UV or LC–MS/MS methods were able to resolve 3- epi -25-OHD3 from 25-OHD3 and thus overestimated total 25-OHD. The cross reactivity of 24R, 25(OH)2 D3 (24S, 25(OH)2 D3 ) ranged from <5% (<5%) to 548% (643%) in ligand binding assays. Both 24-hydroxylated metabolites were resolved by HPLC/UV and LC–MS/MS methods and thus caused no complications in the measurement of 25-OHD. Most antibodies to 25-OHD are known to cross-react with dihydroxylated metabolites but interference in some assays was far greater than expected. This may be related to the anomalous behaviour of exogenously added metabolites in these 25-OHD methods.